Improvement of growth, lipid metabolism and innate immune response in Pacific white shrimp (Penaeus vannamei) post-larvae through enrichment of live feeds with Schizochytrium sp., taurine and inosine monophosphate - Suhyeok Kim; Sanghyun Song; Yeonji Lee; Yein Lee; Young-Mi Lee; Kook-Jin Cho; Kyeong-Jun Lee (PLoS ONE, 2026)
Nutritional deficiencies during the early developmental stages of Penaeus vannamei often lead to poor growth, weak immunity and high mortality. To address these issues, this study investigated the effects of live feeds enriched with Schizochytrium sp. (SCH), taurine and inosine monophosphate (IMP) on the growth, lipid metabolism and immune response of shrimp post-larvae. Two feeding trials were conducted using rotifers (Trial 1) and Artemia (Trial 2) as live feeds. In trial 1, post-larvae (PL1–2) were fed unenriched rotifers (RN) or rotifers enriched with 0.5% SCH (RS), RS + 0.1% taurine (RS + T), RS + 0.1% IMP (RS + I) and 0.5% Chlorella powder (RCL) for 9 days. In trial 2, post-larvae (PL12–14) were fed unenriched Artemia (AN) or Artemia enriched with 0.5% SCH (AS), AS + 0.1% taurine (AS+T), AS + 0.1% IMP (AS+I) and 0.5% Chlorella powder (ACL) for 12 days. In trial 1, growth was significantly higher in RS, RS + T and RS + I groups compared to RN and RCL groups. Survival was significantly higher in RS, RS + T and RS + I groups than in RN group. In trial 2, growth performance was significantly higher in all SCH-enriched groups compared to AN and ACL groups whereas, survival did not differ significantly among the experimental groups. In both trials, whole-body docosahexaenoic acid levels increased markedly in all SCH-supplemented treatments, and the expression of lipid metabolism-related genes ( FAS , FABP , FATP and CPT1 ) and immune-related genes ( lysozyme , crustin , LGBP , Pen-3a and proPO ) was significantly upregulated. These results demonstrate that enrichment of live feeds with SCH effectively enhances growth, lipid utilization and immune function in P. vannamei post-larvae. Furthermore, combined supplementation with taurine and IMP produced synergistic immunostimulatory effects. Overall, SCH-based enrichment can serve as a promising functional nutritional fortifier for shrimp hatchery diets.